MENUMBUHKAN USAHA MELALUI KEGIATAN KELOMPOK USAHA BERSAMA DI KAMPUNG TAMBAK LOROK SEMARANG - Wyati Sadewisasi; Djoko Santoso; Nunik Kusnilawati; Aprih Santoso (TEMATIK, 2019)
In Kampung Tambak Lorok there is a group of PKK women who are a group of housewives in the village area. Problems faced by PKK women in Kampung Tambak Lorok are: (1) Do not have a strong entrepreneurial spirit; (2) A joint business unit for PKK mothers has not yet been formed; (3) Knowledge about cooperatives is still lacking. The purpose of this community service is to improve the skills of the human resources of PKK women to become entrepreneurs and the procedures for establishing joint business groups (KUB) and to increase their entrepreneurial spirit. The community service is carried out using lecture, tutorial and discussion methods. Training and counseling on entrepreneurship, cooperatives, the formation of joint business groups can provide new understanding to PKK mothers that it turns out that entrepreneurship, cooperatives and joint ventures are indispensable in doing business. In this service also practiced making fish pempek. The results show that participants feel interested and interested in practicing making pempek and want to sell it.